2009
DOI: 10.1007/s12011-009-8584-6
|View full text |Cite
|
Sign up to set email alerts
|

Microelements in Stones, Urine, and Hair of Stone Formers: A New Key to the Puzzle of Lithogenesis?

Abstract: The role of trace elements in lithogenesis is still unclear. The aim of this study was to evaluate the levels of elements in urinary stones and in the urine and hair of stone formers to identify these elements that have synergic correlations in studied materials and may contribute to lithogenesis. A total of 219 consecutive patients with idiopathic upper urinary tract stones were prospectively enrolled in the study. Urine and hair samples were collected from all patients. The content of the stone was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…As mentioned above, disruption of the equilibrium of elements is thought to be one of the factors related to disease. Słojewski et al [37] reported a study to evaluate the levels of elements in uroliths from 219 consecutive patients with idiopathic upper urinary tract stones. Significant correlations were obtained among various trace elements in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, disruption of the equilibrium of elements is thought to be one of the factors related to disease. Słojewski et al [37] reported a study to evaluate the levels of elements in uroliths from 219 consecutive patients with idiopathic upper urinary tract stones. Significant correlations were obtained among various trace elements in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the findings of Trinchieri et al [9] reviewed earlier, Meyer and Angino [4] and Munoz and Valiente [15] failed to observe an inhibitory effect of zinc addition on calcium oxalate crystal growth through in vitro experiments. It is possible that zinc replaces calcium in the crystal lattice due to similar charge and molecular size, and promotes phosphate salt deposition [5,18]. Slojewski et al [18] analyzed stone samples from 219 kidney stone formers, and found that stone zinc content was directly correlated with the amount of phosphate salts.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that zinc replaces calcium in the crystal lattice due to similar charge and molecular size, and promotes phosphate salt deposition [5,18]. Slojewski et al [18] analyzed stone samples from 219 kidney stone formers, and found that stone zinc content was directly correlated with the amount of phosphate salts. It is unclear whether this stone-promoting effect occurs at a certain threshold of zinc concentration in urine.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers dealt with investigation of trace elements in urinary stones in relation to kidney stones formation (Atakan et al 2007;Durak et al 1992;Perk et al 2002; Electronic supplementary material The online version of this article (doi:10.1007/s10653-015-9691-2) contains supplementary material, which is available to authorized users. Slojewski et al 2010;Carpentier et al 2011;Abboud 2008b, c); however, conclusions from such investigations are ambiguous and often contradictory (Slojewski 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As far as authors know, only a few studies were published regarding differences in contents of trace element in urinary stones related to geographical conditions (Kuta et al 2012;Pineda-Vargas et al 2009, smoking (Slojewski et al 2009) or to the effect of sex and age (Kuta et al 2012). However, use of urinary stones for biomonitoring can be limited by known mutual association of trace and minor elements with mineral constituents (Giannossi et al 2013;Abboud 2008a;Bazin et al 2007;Kuta et al 2013;Slojewski et al 2010;Wandt and Underhill 1988). These mutual associations then can act as a source of variability in the obtained results and the reason for their ambiguous interpretation.…”
Section: Introductionmentioning
confidence: 99%